Processing method for optimizing corona discharge resistance and charge aggregation of epoxy insulator
By fluorinating the surface of epoxy insulators, a dense fluorinated layer is formed, which solves the corona discharge problem of epoxy insulators in high voltage environments, significantly improves its corona resistance performance in alternative insulating gases, and promotes the Development of environmentally friendly insulation systems.
Patent Information
- Application Number
- CN202411384816.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
Epoxy insulators are prone to corona discharge in high voltage and high electric field environments, which damages the insulating materials and leads to electrical energy loss and electromagnetic interference. The insulation performance of existing alternative insulating gases is not as good as SF6, so it is necessary to improve the epoxy insulators in these gases. Corona discharge resistance to reduce greenhouse gas emissions and environmental impacts.
By fluorinating the surface of the epoxy insulator, fluorinating the surface of the fluorine-containing mixed gas is used in a closed reactor, a dense fluorinated layer is formed to accelerate charge dissipation, improve insulation performance, and in a multi-needle-flat plate electrode system Perform corona testing to evaluate performance.
It significantly improves the corona discharge resistance of epoxy insulators in alternative insulating gases, reduces the frequency and severity of corona discharge, extends the service life of the equipment, and promotes the development of SF6-free gas insulation systems and replaces gases. Widely used.
Smart Images

Figure CN119274900A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulation protection of power system equipment, and in particular relates to a processing method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators. Background Art
[0002] Epoxy insulators are widely used in high-voltage power equipment due to their excellent electrical properties and mechanical strength. However, in high-voltage and high-electric field working environments, corona discharge is prone to occur, which not only damages the insulating material, but also causes power loss and electromagnetic interference. Therefore, the corona discharge resistance of epoxy insulation still needs to be further improved. By improving the corona discharge resistance of epoxy insulators, the occurrence of partial discharge can be effectively reduced and the service life of the equipment can be extended, which is of great significance for ensuring the stable operation of the power system.
[0003] The choice of insulating gas has a significant impact on the corona discharge resistance of epoxy insulators. Sulfur hexafluoride (SF6) is a commonly used electrical insulating gas, widely used in high-voltage power transmission and distribution equipment, with excellent insulation performance and arc extinguishing ability. However, SF6 has a strong greenhouse effect. In the context of achieving the carbon peak target to cope with global climate change, how to reduce carbon emissions while ensuring the reliability of power supply has become an urgent problem to be solved. Therefore, the importance of developing SF6-free insulating gas systems has become increasingly prominent, which can not only reduce greenhouse gas emissions and promote the realization of the carbon peak target, but also reduce the long-term impact on the environment. At present, some potential insulating gas alternatives have emerged, such as air insulation, nitrogen-oxygen mixed gas, and fluorinated carbon compounds. However, the insulating performance of alternative gases is usually not as good as SF6. Therefore, it is particularly important to improve the corona discharge resistance of epoxy insulators in these gases. By optimizing the material composition and surface treatment, corona discharge can be reduced while using environmentally friendly insulating gases, maintenance costs can be reduced, and safe and reliable operation of equipment can be ensured.
[0004] In summary, the improvement of the corona discharge resistance of epoxy insulators in insulating gas is of great significance to the stability, safety and environmental protection of the power system. Through technical improvements and material optimization, more efficient and reliable power system operation can be achieved. The technical problem to be solved by the present invention is: Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a treatment method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators, which can effectively accelerate the charge dissipation on the surface of epoxy insulators, improve the corona discharge resistance of epoxy insulators in insulating gas, and promote the development of environmentally friendly gas insulation systems.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0007] The treatment method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators is as follows:
[0008] 1. Prepare epoxy insulation samples;
[0009] 2. Prepare a closed reactor;
[0010] 3. Prepare fluorine-containing mixed gas;
[0011] 4. Fluoridation treatment;
[0012] 5. Take out the sample after cooling;
[0013] 6. Analyze the characteristics of the fluorinated layer;
[0014] 7. Evaluate charge accumulation and corona discharge performance;
[0015] 8. Conduct corona discharge test;
[0016] Preferably, the epoxy insulation sample comprises bisphenol A diglycidyl ether (DGEBA) type epoxy resin cured by methyltetrahydrophthalic anhydride (MTHPA) filled with alumina particles; the epoxy insulation sample is a disc insulator.
[0017] The epoxy insulation specimens are circular specimens with a thickness of 2 mm and a diameter of 50 mm or 80 mm.
[0018] The production process is as follows: bisphenol A diglycidyl ether and methyl tetrahydrophthalic anhydride are uniformly mixed in a weight ratio of 1:1; during the mixing process, the two materials are ensured to be fully mixed; the mixed material should be in a uniform liquid state without obvious stratification or precipitation;
[0019] The mixed materials are subjected to vacuum degassing treatment; vacuum degassing removes bubbles and volatile impurities in the materials and improves the quality and performance of the samples;
[0020] The degassed material is vacuum poured into a stainless steel mold; the pouring process should be done slowly to avoid bubbles and turbulence;
[0021] The poured samples were cured at 140°C for 9 hours. During the curing process, the temperature was kept stable to avoid excessive temperature fluctuations. After curing, the samples should have a certain hardness and strength, and the surface should be smooth and flat.
[0022] After curing, clean the sample to remove the release agent on its surface;
[0023] The cleaned samples were dried in a vacuum oven at 50°C.
[0024] Preferably, the fluorine-containing mixed gas comprises fluorine gas (F2) and an inert gas (nitrogen or helium); the volume percentage of fluorine gas in the fluorine-containing mixed gas is 2% to 50%;
[0025] Before using the reactor, replace the gas in the reactor with high-purity nitrogen at least 3 times to ensure that there is no other impurity gas in the reactor.
[0026] Preferably, the process of fluorination treatment is: placing the epoxy insulation sample into a reactor; heating the reactor to a set temperature of 50° C.; slowly introducing a fluorine-containing mixed gas to maintain a reaction pressure of 1 bar; and the reaction time is 30 minutes.
[0027] Preferably, the reaction temperature of the fluorination treatment is from room temperature to 100°C.
[0028] Preferably, the reaction pressure of the fluorination treatment is 0.1-2 bar.
[0029] Preferably, the reaction time of the fluorination treatment is 10 min-24 h.
[0030] Preferably, the fluorination process is:
[0031] Place the prepared epoxy insulation samples into the reactor; the samples should be evenly distributed in the reactor to avoid accumulation and overlap to ensure uniformity of fluorination treatment;
[0032] Heat the reactor to the set temperature, the temperature range is: room temperature to 100 ° C;
[0033] Slowly introduce the fluorine-containing mixed gas to maintain the reaction pressure at 0.1-2 bar. The pressure control should be adjusted according to the pressure resistance of the reactor and the requirements of fluorination treatment;
[0034] The fluorine gas concentration is 12.5% of the fluorine-nitrogen mixed gas, and the reaction time is 10 minutes to 24 hours. The length of the reaction time should be adjusted according to the requirements of the fluorination treatment and the performance of the sample.
[0035] Preferably, the process of taking out the sample after cooling is: after the reaction is completed, turn off the heating source and cool naturally to room temperature; open the reactor and take out the epoxy insulation sample after fluorination treatment.
[0036] Preferably, analyzing the characteristics of the fluorinated layer refers to observing the thickness and surface morphology of the fluorinated layer using a scanning electron microscope, and the process is as follows:
[0037] The SEM cross-section samples were prepared by low-temperature brittle fracture in liquid nitrogen. Low-temperature brittle fracture prevented the samples from being affected by thermal and mechanical stresses during the preparation process, and maintained the original structure and performance of the samples. During the brittle fracture process, the samples were quickly immersed in liquid nitrogen, and then gently tapped with a hammer or other tool to break them. The broken samples should be immediately observed by SEM to avoid oxidation and contamination on the sample surface.
[0038] The chemical composition and structure of the fluorinated layer were analyzed by attenuated total reflection infrared spectroscopy; attenuated total reflection infrared spectroscopy can provide chemical information on the surface of the sample and reveal the effect of fluorination treatment on the chemical structure of epoxy resin;
[0039] Attenuated total reflection infrared spectroscopy uses germanium crystal as the reflective crystal for testing, and the spectrum is the average of 128 scans; multiple scans can improve the signal-to-noise ratio and accuracy of the spectrum and reduce the impact of noise and errors;
[0040] Ensure that the thickness of the fluoride layer is between 0.2-2 μm.
[0041] Preferably, the process for evaluating charge accumulation and corona discharge performance is:
[0042] The sample is charged by gate control; the sample is quickly transferred to the bottom of the potential detector to measure the surface potential; the data is transmitted to the computer through a multi-function meter to record the charge dissipation rate.
[0043] Preferably, the evaluation of charge accumulation and corona discharge performance is carried out in a plexiglass chamber filled with air, carbon dioxide or C4F7N / CO2 mixed gas; the sample is corona treated using a multi-needle-plate electrode system; the surface changes of the sample during the corona discharge process are recorded to evaluate the corona erosion.
[0044] The procedure for evaluating charge accumulation and corona discharge performance is:
[0045] The sample is charged by gate control. Gate control charging can provide a uniform electric field to avoid local discharge and charge accumulation on the surface of the sample. The charge transport process inside the material to the ground electrode can be described by the current conduction equation, Poisson's equation and charge continuity equation:
[0046] j e (x, t) = γE(x, t) (1);
[0047]
[0048]
[0049] in,
[0050]
[0051]
[0052] Here, x is the medium depth in meters; t is the time in seconds; γ is the Poole-Frenkel conductivity of the medium material in S·m -1 ; When there is no external electric field, the bulk conductivity of the medium at temperature T is γ0(T), the unit is S·m -1 ; e is the electron charge, the unit is C; j e (x, t) is the current density, in A·m -2 ; q(x,t) is the charge density, the unit is C·m -3 ; E(x,t) is the electric field strength, the unit is V·m -1 .
[0053] Before charging, the sample should be placed in a suitable electrode system to ensure good contact between the sample and the electrode;
[0054] The experimental conditions were set as follows: needle voltage: 10 kV, grid voltage: 2 kV, charging time: 5 minutes;
[0055] Quickly transfer the sample to the bottom of the potential detector to measure the surface potential; the potential detector should have the characteristics of high sensitivity and fast response, and be able to accurately measure the potential change on the surface of the sample; during the measurement process, the distance between the sample and the potential detector should be kept stable to avoid the influence of distance changes on the measurement results;
[0056] Use a multi-function meter to transfer the measured data to a computer to record the charge dissipation rate; the multi-function meter should have the characteristics of high precision and high stability, and be able to accurately record the potential change and charge dissipation rate on the surface of the sample; when recording data, attention should be paid to the accuracy and reliability of the data to avoid data errors and losses;
[0057] The charge accumulation and corona discharge performance were evaluated in a plexiglass chamber filled with air, carbon dioxide or C4F7N / CO2 mixed gas; the samples were corona treated using a multi-needle-plate electrode system; the surface changes of the samples during the corona discharge process were recorded and the corona erosion was evaluated;
[0058] The evaluation was performed in a plexiglass chamber filled with air, carbon dioxide, or a C4F7N / CO2 mixture;
[0059] The sample is corona treated using a multi-needle-plate electrode system; the multi-needle-plate electrode system is used to provide a uniform electric field to avoid partial discharge and corona discharge on the surface of the sample; before corona treatment, the sample is placed in a suitable electrode system to ensure that the distance and angle between the sample and the electrode meet the requirements;
[0060] The size of the upper electrode plate is 380×320mm, with a total of 280 tungsten needles evenly distributed on the upper electrode plate. The grounded stainless steel electrode consists of a fixed frame plate and a rotatable disc. The sample is placed on the disc and rotates at a speed of 1 circle per minute.
[0061] The electrode system was placed in a sealed plexiglass chamber. The original epoxy resin sample and the surface fluorinated sample were corona treated at room temperature. The gas in the chamber was evacuated and filled with 0.1MPa high-purity nitrogen. An AC voltage of 50Hz and 14kV was applied to the high-voltage electrode. The gas in the chamber was replaced every 12 hours, and the total treatment time was 120h.
[0062] Preferably, the corona discharge test is:
[0063] Ultrasonic cleaning: ultrasonic cleaning is performed on the original samples and fluorinated samples after corona treatment; ultrasonic cleaning can remove pollutants and degradation products on the surface of the samples, and improve the surface cleanliness and performance of the samples; during the cleaning process, appropriate cleaning agents and cleaning time should be selected to avoid the cleaning agent affecting the performance of the samples;
[0064] Water contact angle measurement: measure the water contact angle of the original sample; the water contact angle is an important indicator to measure the wettability of the sample surface. The smaller the water contact angle, the better the wettability of the sample surface; when measuring the water contact angle, deionized water should be used as the test liquid, drop water on the sample surface, and then use a contact angle meter to measure the contact angle between the water drop and the sample surface; measure the water contact angle of the sample after ultrasonic cleaning; the surface of the sample after ultrasonic cleaning may change, so the water contact angle needs to be measured again to evaluate the cleaning effect and the surface performance of the sample;
[0065] Corona resistance evaluation: Compare the contact angles of samples under different treatment conditions to evaluate the corona resistance of the fluorinated layer; by comparing the water contact angles of the original sample, the fluorinated sample and the sample after ultrasonic cleaning, the effect of the fluorinated layer on the wettability of the sample surface and the corona resistance of the fluorinated layer can be evaluated; generally speaking, the fluorinated layer can reduce the water contact angle on the sample surface, improve the surface wettability of the sample, and also improve the corona resistance of the sample.
[0066] The SF6 is the most commonly used insulating medium in gas-insulated equipment, but its strong greenhouse effect limits its use in gas-insulated equipment. At present, some alternative gases have been tested in pilot projects and show good application prospects. However, the insulation performance of alternative gases is usually not as good as SF6, so it is particularly important to improve the corona discharge resistance of epoxy insulators in these gases. By optimizing the material composition and surface treatment, it is possible to ensure the safe and reliable operation of the equipment while using environmentally friendly insulating gases.
[0067] The present invention can achieve the following beneficial effects:
[0068] 1) The present invention adopts a gas phase modification method with simple process, mature technology and extremely effective, in which only the epoxy insulation surface layer is changed, while the matrix itself does not change at all, and the fluorinated surface layer and the non-fluorinated inner layer are "organically (chemically) combined" as a whole;
[0069] 2) The process steps are simple, the controllability is good, the economic cost is low, and the epoxy insulation parts with complex shapes and arbitrary sizes can be fluorinated in batches and uniformly, which is particularly suitable for commercial applications.
[0070] 3) The method of the present invention can significantly improve the corona discharge resistance of epoxy insulation in alternative insulating gases under a wide range of fluorination conditions, has a wide range of applications, and is good in practicality, and can promote the development of SF6-free gas insulation systems and the widespread application of alternative gases.
[0071] 4) The present invention performs surface fluorination modification on epoxy insulation, which is related to high-voltage power transmission and distribution projects. In a closed reactor, the present invention uses a mixed gas composed of fluorine gas and other inert gases to perform fluorination treatment on the surface of epoxy insulation samples for a certain period of time under corresponding temperature, time and pressure conditions, so that the surface has suitable physical and chemical properties, accelerates the decay of the surface potential of epoxy insulation, and improves the corona discharge resistance and charge accumulation of epoxy insulation in insulating gas.
[0072] 5) Existing public methods are also used to improve the corona discharge resistance of epoxy insulation, such as adding inorganic particles to epoxy insulation. However, most studies have adopted the single-needle flat plate electrode system defined by IEC 60343 or proposed by the International Large Power Grid Working Group. The gap between the needle tip and the sample surface of this system is small or even in direct contact. Strong discharge will form uneven annular damage on the sample surface, making it difficult to conduct detailed research on the aging mechanism and performance changes of the material. The present invention uses a multi-needle-plate electrode system. The gap between the needle electrode and the sample surface is large, and the resulting aging area has a certain uniformity.
[0073] 6) The direct fluorination method has many advantages, such as the ability to uniformly batch process epoxy insulators of various shapes and sizes. The fluorinated layer formed by direct fluorination has long-term stability and excellent aging performance. The fluorination process of this method is simple, safe, reliable, and low-cost. It is suitable for epoxy insulation structures of various shapes and sizes, and significantly improves their discharge resistance, and has broad commercial application potential.
[0074] 7) The present invention proposes a surface fluorination modification technology, which performs fluorination treatment on the surface of epoxy insulators to form a dense fluorination layer, significantly improving their corona discharge resistance in different alternative gas environments, in order to promote the development of SF6-free gas insulation systems and the use of alternative gases, and help achieve low-carbon and environmental protection goals. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0076] Figure 1 Schematic diagram of the fluorination treatment system of the method of the present invention;
[0077] Figure 2 The SEM cross-sectional imaging and surface imaging of the epoxy insulation sample after being treated by the method of the present invention;
[0078] Figure 3 ATR-IR spectra of epoxy insulation samples before and after treatment by the method of the present invention;
[0079] Figure 4 Schematic diagram of a device for measuring sample surface potential decay in the method of the present invention;
[0080] Figure 5 It is the normalized curve of sample surface potential decay in the method of the present invention (comparison between the original epoxy insulation sample and the fluorinated epoxy insulation sample);
[0081] Figure 6 A multi-needle-plate electrode system for corona treatment of epoxy samples in the method of the present invention;
[0082] Figure 7 This is the SEM cross-sectional imaging of the untreated epoxy sample after corona treatment in the method of the present invention;
[0083] Figure 8 This is the SEM cross-sectional imaging of the fluorinated epoxy sample after corona in the method of the present invention. DETAILED DESCRIPTION
[0084] The preferred solution is Figures 1 to 8 As shown, the treatment method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators is as follows:
[0085] 1. Prepare epoxy insulation samples
[0086] 1. Raw material selection: Bisphenol A diglycidyl ether epoxy resin (DGEBA, LE-9218) and methyltetrahydrophthalic anhydride curing agent (MTHPA, LH-9218) are selected. These two materials have good electrical insulation, thermal and mechanical properties and are widely used in the field of high voltage insulation.
[0087] 2. Sample preparation: Mix DGEBA and MTHPA in a weight ratio of 1:1. During the mixing process, mechanical stirring or ultrasonic stirring can be used to ensure that the two materials are fully mixed. The mixed material should be in a uniform liquid state without obvious stratification or precipitation.
[0088] The mixed materials are vacuum degassed. Vacuum degassing can remove bubbles and volatile impurities in the materials and improve the quality and performance of the samples. The time and pressure of vacuum degassing should be adjusted according to the specific situation. Generally, the degassing process can be carried out for several hours at a lower pressure (such as 1-5mmHg).
[0089] The degassed material is vacuum poured into a stainless steel mold. The stainless steel mold should have good flatness and dimensional accuracy to ensure that the shape and size of the sample meet the requirements. The pouring process should be carried out slowly to avoid bubbles and turbulence.
[0090] The poured sample is cured at 140°C for 9 hours. During the curing process, the temperature should be kept stable to avoid excessive temperature fluctuations. After curing, the sample should have a certain hardness and strength, and the surface should be smooth and flat.
[0091] 3. Sample processing: After curing, clean the sample and remove the release agent on its surface. The release agent may affect the surface properties of the sample and the subsequent fluorination treatment effect, so it must be removed thoroughly. The cleaning method can be solvent cleaning, mechanical grinding or chemical treatment, etc., which should be selected according to the properties of the release agent and the requirements of the sample. The cleaned sample is vacuum dried in a vacuum oven at 50°C. The drying process can remove residual moisture and volatile impurities in the sample and improve the dryness and stability of the sample. The drying time should be adjusted according to the thickness and size of the sample, generally between several hours and tens of hours.
[0092] 4. Sample specifications: Epoxy insulation samples can be disc insulators, with a thickness of 2mm and a circular sample of 50mm or 80mm in diameter. Such specifications and dimensions are convenient for subsequent fluorination treatment and performance testing, and also meet the size requirements in actual applications.
[0093] 2. Prepare the closed reactor
[0094] 1. Reactor selection: Choose a suitable stainless steel reactor. The volume and size of the reactor should be selected according to the number and size of the samples to ensure that the samples can be fully expanded in the reactor and there is enough space for fluorination treatment.
[0095] The reactor should have good sealing and pressure resistance, and be able to withstand the pressure and temperature changes during the fluorination process. At the same time, the reactor should be equipped with corresponding heating, cooling, gas inlet and outlet, and pressure control devices to facilitate the operation and control of the fluorination process.
[0096] 2. Gas replacement: Use high-purity nitrogen to replace the gas in the reactor at least 3 times before use. The purpose of gas replacement is to remove the air and other impurity gases in the reactor to ensure that the fluorination process is carried out in a pure atmosphere. Each time the gas is replaced, the pressure in the reactor should be increased to a certain value (such as 0.1-0.5MPa), and then the pressure should be slowly released. Repeat this process several times to ensure that the gas in the reactor is fully replaced.
[0097] 3. Configure fluorine-containing mixed gas
[0098] 1. Gas selection: Fluorine-containing mixed gases include fluorine (F2) and inert gas (nitrogen or helium). Fluorine is the main gas for fluorination treatment. It has extremely high reactivity and oxidizing ability. It can replace hydrogen atoms in epoxy resin and introduce fluorine atoms, thereby changing the surface properties of epoxy resin. Inert gas plays a diluting and protective role to prevent violent reactions and safety problems caused by excessive fluorine concentration.
[0099] 2. Gas ratio: The volume percentage of fluorine gas in the fluorine-containing mixed gas is 2% to 50%. The ratio of fluorine gas should be adjusted according to the specific fluorination treatment requirements and the properties of the epoxy resin. Generally speaking, the higher the fluorine gas ratio, the more obvious the fluorination treatment effect, but it will also increase the severity of the reaction and safety risks. Therefore, when determining the fluorine gas ratio, factors such as the effect, safety and cost of the fluorination treatment should be comprehensively considered.
[0100] 4. Fluoridation treatment
[0101] 1. Sample placement: Place the prepared epoxy insulation samples into the reactor. The samples should be evenly distributed in the reactor to avoid accumulation and overlap to ensure uniformity of fluorination treatment.
[0102] 2. Temperature control: Heat the reactor to the set temperature, the temperature range is room temperature-100℃, preferably 55℃. The temperature should be adjusted according to the properties of the epoxy resin and the requirements of the fluorination treatment. Generally speaking, the higher the temperature, the faster the fluorination reaction, but it also increases the possibility of molecular chain breakage and cross-linking, affecting the performance of the sample. Therefore, when determining the heating temperature, factors such as the speed of the fluorination reaction, the performance and safety of the sample should be considered comprehensively.
[0103] 3. Pressure control: Slowly introduce the fluorine-containing mixed gas to maintain the reaction pressure at 0.1-2 bar, preferably 0.1 MPa. The pressure control should be adjusted according to the pressure resistance of the reactor and the requirements of the fluorination treatment. Generally speaking, the higher the pressure, the faster the fluorination reaction, but it also increases the safety risk. Therefore, when determining the reaction pressure, factors such as the speed, safety and cost of the fluorination reaction should be considered comprehensively.
[0104] 4. Gas concentration: The fluorine gas concentration is 12.5% of the fluorine-nitrogen mixed gas, and the reaction time is 10min-24h, preferably 30 minutes. The length of the reaction time should be adjusted according to the requirements of the fluorination treatment and the performance of the sample. Generally speaking, the longer the reaction time, the more obvious the effect of the fluorination treatment, but it will also increase the performance changes and safety risks of the sample. Therefore, when determining the reaction time, factors such as the effect of the fluorination treatment, the performance and safety of the sample should be considered comprehensively.
[0105] 5. Take out the sample after cooling
[0106] 1. Cooling process: After the reaction is completed, turn off the heating source and let the reactor cool naturally to room temperature. Natural cooling can avoid changes in sample performance and stress concentration caused by a sudden drop in temperature. During the cooling process, the pressure in the reactor should be kept stable to avoid excessive pressure changes.
[0107] 2. Sample removal: Open the reactor and take out the epoxy insulation sample after fluorination treatment. Be careful when taking out the sample to avoid damage or contamination. After the sample is taken out, subsequent analysis and testing should be carried out immediately to ensure the performance and quality of the sample.
[0108] 6. Analysis of the characteristics of the fluorinated layer
[0109] 1. SEM observation: Use a scanning electron microscope (SEM) to observe the thickness of the fluoride layer and its surface morphology. SEM can provide high-resolution images that clearly show the thickness and surface morphology of the fluoride layer. Before observation, the sample should be properly processed, such as cutting, polishing and gold plating, to improve the observation effect.
[0110] The SEM cross-section samples were prepared by low-temperature brittle fracture in liquid nitrogen. Low-temperature brittle fracture can avoid the influence of thermal stress and mechanical stress on the sample during the preparation process, and maintain the original structure and performance of the sample. During the brittle fracture process, the sample should be quickly immersed in liquid nitrogen, and then gently tapped with a hammer or other tools to break it. The broken sample should be immediately observed by SEM to avoid oxidation and contamination on the surface of the sample.
[0111] 2. ATR-IR analysis: Attenuated total reflection infrared (ATR-IR) spectroscopy is used to analyze the chemical composition and structure of the fluorinated layer. ATR-IR can provide chemical information on the surface of the sample and reveal the effect of fluorination treatment on the chemical structure of the epoxy resin. Before analysis, the sample should be properly treated, such as cleaning and drying, to improve the analysis effect. The ATR-IR spectrum is tested using a germanium crystal as a reflective crystal, and the spectrum is the average of 128 scans. Multiple scans can improve the signal-to-noise ratio and accuracy of the spectrum and reduce the impact of noise and errors.
[0112] 3. Thickness control: Ensure that the thickness of the fluorinated layer is between 0.2-2μm, preferably 0.4-1μm. The thickness of the fluorinated layer should be adjusted according to the specific application requirements and the performance of the sample. Generally speaking, the thicker the fluorinated layer, the better the corona resistance of the sample, but it will also increase the cost and weight of the sample. Therefore, when determining the thickness of the fluorinated layer, factors such as the performance, cost and weight of the sample should be considered comprehensively.
[0113] VII. Evaluation of Charge Accumulation and Corona Discharge Performance
[0114] 1. Charging method: The sample is charged by gate control. Gate control charging can provide a uniform electric field to avoid local discharge and charge accumulation on the surface of the sample.
[0115] The sample is charged by gate control. Gate control charging can provide a uniform electric field to avoid local discharge and charge accumulation on the surface of the sample. Inside the material, the charge transport process to the ground electrode is described by the current conduction equation, Poisson's equation and charge continuity equation:
[0116] j e (x, t) = γE(x, t) (1);
[0117]
[0118]
[0119] in,
[0120]
[0121]
[0122] Where x is the medium depth in m; t is the time in s; γ is the Poole-Frenkel conductivity of the medium material in S·m -1 ; When there is no external electric field, the bulk conductivity of the medium at temperature T is γ0(T), the unit is S·m -1 ; e is the electron charge, the unit is C; j e(x, t) is the current density, in A·m -2 ; q(x,t) is the charge density, the unit is C·m -3 ; E(x,t) is the electric field strength, the unit is V·m -1 .
[0123] Before charging, the sample should be placed in a suitable electrode system to ensure good contact between the sample and the electrodes.
[0124] 2. The experimental conditions are set as: needle voltage –10kV, grid voltage –2kV, and charging time is 5 minutes. The selection of charging parameters should be adjusted according to the size and performance of the sample to ensure that the sample can be fully charged and will not be broken down or damaged.
[0125] 3. Potential measurement: quickly transfer the sample to the bottom of the potential detector to measure the surface potential. The potential detector should have the characteristics of high sensitivity and fast response, and be able to accurately measure the potential changes on the surface of the sample. During the measurement process, the distance between the sample and the potential detector should be kept stable to avoid the influence of distance changes on the measurement results.
[0126] The multi-function meter is used to transmit the measured data to the computer to record the charge dissipation rate. The multi-function meter should have the characteristics of high precision and high stability, and can accurately record the potential change and charge dissipation rate on the surface of the sample. When recording data, attention should be paid to the accuracy and reliability of the data to avoid data errors and losses.
[0127] 4. Environmental control: The evaluation is carried out in a plexiglass chamber filled with air, carbon dioxide or C4F7N / CO2 mixed gas, preferably in a pure N2 atmosphere. The choice of environmental gas should be adjusted according to the specific application requirements and the performance of the sample. Generally speaking, pure N2 atmosphere has high stability and insulation properties, which can reduce charge accumulation and corona discharge on the surface of the sample. When conducting the evaluation, the purity and pressure of the environmental gas should be kept stable to avoid the impact of gas contamination and pressure changes on the evaluation results.
[0128] 5. Corona treatment: Use a multi-needle-plate electrode system to perform corona treatment on the sample. The multi-needle-plate electrode system can provide a uniform electric field to avoid partial discharge and corona discharge on the surface of the sample. Before corona treatment, the sample should be placed in a suitable electrode system to ensure that the distance and angle between the sample and the electrode meet the requirements.
[0129] The size of the upper electrode plate is 380×320mm, with a total of 280 tungsten needles evenly distributed on the upper electrode plate. The grounded stainless steel electrode consists of a fixed frame plate and a rotatable disc. The sample is placed on the disc and rotates at a speed of 1 circle per minute. Such an electrode system can ensure that the sample is subjected to a uniform electric field during the corona treatment process, thereby improving the effect and uniformity of the corona treatment.
[0130] The electrode system is placed in a sealed organic glass chamber, and the original epoxy resin sample and the surface fluorinated sample are corona treated at room temperature. The gas in the chamber is evacuated and filled with 0.1MPa high-purity nitrogen. An AC voltage of 50Hz and 14kV is applied to the high-voltage electrode. The gas in the chamber is replaced every 12 hours, and the total treatment time is 120h. The parameters of the corona treatment should be adjusted according to the size and performance of the sample to ensure that the sample can be fully corona treated and will not be broken down or damaged.
[0131] 6. Evaluation method: record the surface changes of the sample during the corona discharge process and evaluate the corona erosion. During the corona treatment process, the surface changes of the sample should be closely observed, such as color change, crack generation, surface roughness increase, etc. At the same time, SEM, ATR-IR and other analysis methods should be used to analyze the surface morphology and chemical composition of the sample to evaluate the degree and impact of corona erosion.
[0132] 8. Conduct corona discharge test
[0133] 1. Ultrasonic cleaning: Perform ultrasonic cleaning on the original sample and fluorinated sample after corona treatment. Ultrasonic cleaning can remove pollutants and degradation products on the surface of the sample, and improve the surface cleanliness and performance of the sample. During the cleaning process, the appropriate cleaning agent and cleaning time should be selected to avoid the cleaning agent affecting the performance of the sample.
[0134] 2. Water contact angle measurement: measure the water contact angle of the original sample. The water contact angle is an important indicator to measure the wettability of the sample surface. The smaller the water contact angle, the better the wettability of the sample surface. When measuring the water contact angle, deionized water should be used as the test liquid, drop water on the sample surface, and then use a contact angle meter to measure the contact angle between the water drop and the sample surface.
[0135] Measure the water contact angle of the sample after ultrasonic cleaning. The surface of the sample may change after ultrasonic cleaning, so it is necessary to measure the water contact angle again to evaluate the cleaning effect and the surface properties of the sample.
[0136] 3. Corona resistance evaluation: Compare the contact angles of the samples under different treatment conditions to evaluate the corona resistance of the fluorinated layer. By comparing the water contact angles of the original sample, the fluorinated sample, and the sample after ultrasonic cleaning, the effect of the fluorinated layer on the wettability of the sample surface and the corona resistance of the fluorinated layer can be evaluated. Generally speaking, the fluorinated layer can reduce the water contact angle on the sample surface, improve the surface wettability of the sample, and also improve the corona resistance of the sample.
[0137] The present invention includes the following embodiments:
[0138] Embodiment 1:
[0139] like Figure 1 As shown, this embodiment provides a treatment method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators in insulating gas, including an epoxy insulation sample, and performing a fluorination treatment process on the epoxy insulation sample to improve the corona discharge resistance and charge accumulation of the epoxy insulation sample in insulating gas. The epoxy insulation sample is an alumina-filled epoxy resin material supporting an insulating gas switchgear, and the fluorination treatment process is to perform a fluorination treatment reaction on the epoxy insulation sample using a fluorine-containing mixed gas in a closed reactor.
[0140] The epoxy resin material is bisphenol A diglycidyl ether epoxy resin cured by methyltetrahydrophthalic anhydride filled with aluminum oxide particles, and the epoxy insulation sample is a disc insulator.
[0141] The fluorine-containing mixed gas includes fluorine gas and inert gas. The volume percentage of the fluorine gas in the fluorine-containing mixed gas is 2% to 50%, and the inert gas is nitrogen or helium.
[0142] The reaction temperature of the fluorination treatment process is from room temperature to 100°C.
[0143] The reaction pressure of the fluorination process is 0.1-2 bar.
[0144] The reaction time of the fluorination treatment process is 10min-24h.
[0145] The fluorine-containing mixed gas includes fluorine gas and nitrogen gas. The volume percentage of fluorine gas in the fluorine-containing mixed gas is 10%. The reaction temperature of the fluorination treatment process is 50° C., the pressure is 1 bar, and the time is 30 minutes.
[0146] The room temperature is set to be no less than 0 degrees by default.
[0147] Furthermore, the epoxy insulation is an epoxy resin material filled with alumina particles that supports the insulating gas switchgear.
[0148] Furthermore, after fluorination treatment, a micrometer-scale fluorinated surface layer is formed on the epoxy insulation surface.
[0149] Furthermore, the thickness of the fluorinated surface layer is 0.2-2 μm.
[0150] As a preferred technical solution, the thickness of the fluorinated surface layer is 0.4-1 μm.
[0151] Embodiment 2:
[0152] This embodiment is optimized based on embodiment 1.
[0153] The epoxy insulator is a disc insulator.
[0154] The epoxy insulation sample is made of bisphenol A diglycidyl ether (DGEBA) epoxy resin cured by methyltetrahydrophthalic anhydride (MTHPA) filled with alumina particles.
[0155] The epoxy insulation sample is a circular specimen with a thickness of 2 mm and a diameter of 50 or 80 mm.
[0156] The closed reactor is a fluorination test chamber.
[0157] Direct fluorination of the disc insulator and the epoxy insulation coupon was carried out using the fluorination process flow.
[0158] Further preferably, the reaction gas used in the fluorination treatment process is a F2 / N2 mixed gas with a fluorine gas volume fraction of 10%, and the reaction pressure, temperature and time are 1 bar, 50°C and 30 min respectively.
[0159] The fluorination treatment process adopts an industrial fluorination process. First, the epoxy insulation sample is placed in a fluorination barrel, and then the fluorination barrel is heated. When the temperature inside reaches the set temperature of 50°C, high-purity nitrogen is used to replace the gas in the fluorination barrel at least 3 times, and finally the reaction mixed gas is slowly introduced.
[0160] Since the epoxy insulation sample and the disc insulator are made of the same material, the present invention uses the epoxy insulation sample that is synchronously fluorinated with the disc insulator to analyze the physicochemical characteristics of the fluorinated layer of the disc insulator.
[0161] The thickness and surface morphology of the fluorinated layer were observed with the help of scanning electron microscopy (SEM), and the chemical composition and structure of the fluorinated layer were analyzed by attenuated total reflection infrared (ATR-IR) spectroscopy.
[0162] like Figure 2 As shown, it was observed that the fluorination treatment increased the surface roughness of the epoxy sample and formed a fluorinated layer with a thickness of about 0.76 μm.
[0163] like Figure 3 As shown in Figure 2, in addition to the hydroxyl absorption, fluorination significantly reduces the infrared absorption of the epoxy matrix in the range of 900-1300 cm -1 In the range of 2000, a strong C-F stretching absorption band was generated, and the original C=O absorption peak (1730cm -1 ) was significantly weakened, and a new C=O absorption appeared on its high wave number side. This indicates that the fluorine atom replaced the hydrogen atom in the surface layer and added to the conjugated double bond of the benzene ring in the surface layer.
[0164] Embodiment 3:
[0165] like Figure 4 As shown in the figure, the surface potential decay of epoxy samples before and after fluorination is measured. First, the sample is charged by gate control, and then the sample is quickly transferred to the bottom of the potential detector. The surface potential is measured by the electrostatic potentiometer, and the data is transmitted to the computer through the multi-function meter.
[0166] like Figure 5 As shown, under the same charging voltage, the surface charge dissipation rate of the fluorinated epoxy resin sample first dissipates rapidly and then slowly with time, which is much greater than that of the non-fluorinated sample, and the overall ability to inhibit charge accumulation is improved.
[0167] Embodiment 4:
[0168] like Figure 6 As shown, the epoxy specimens were corona treated using a multi-needle-plate electrode system in an air-filled plexiglass chamber.
[0169] like Figure 7 As shown, during the corona discharge process, the original sample is continuously etched, and the volatile degradation products produced enter the gas phase and cannot remain on the sample surface. The existence of the degradation layer cannot be clearly observed in the figure.
[0170] like Figure 8 As shown in the figure, corona erosion does not generate volatile degradation products on the surface of the fluorinated sample. During the corona treatment process, the fluorinated layer is extremely stable under the action of ultraviolet radiation and high-energy charged particles. The fluorinated layer has a high barrier to corona discharge, and fluorination improves the corona discharge resistance of epoxy insulation in air.
[0171] Embodiment 5:
[0172] This embodiment is optimized based on embodiment 4.
[0173] The corona treated original and fluorinated samples were ultrasonically cleaned, and the static contact angle of deionized water on the samples was measured to evaluate the wettability of the samples. (The epoxy original samples and fluorinated samples before and after corona treatment will be recorded as samples V, F and VC, FC respectively. After ultrasonic washing, samples VC and FC will be recorded as samples VCR and FCR).
[0174] Sample V VC VCR F FC FCR Water contact angle(°) 99.56 16.82 61.25 55.62 50.24 49.05
[0175] As shown in the table, the water contact angle of sample VC is much smaller than that of sample V. After ultrasonic cleaning, the contact angle of sample VCR returns to 61.25°, because the degradation products generated by the corona of the original sample are partially dissolved during ultrasonic cleaning. Samples FC and FCR have almost the same contact angle. After the fluorinated samples treated with corona are rinsed with water, their surface properties have hardly changed, indicating that the surface layer of the fluorinated samples has almost no soluble degradation products generated during the corona treatment process. The fluorinated layer has a high barrier to corona discharge, and the corona resistance performance is improved.
[0176] Embodiment 6:
[0177] The epoxy samples were corona treated using a multi-needle-plate electrode system in a plexiglass chamber filled with carbon dioxide.
[0178] After the fluorinated samples treated with corona were rinsed with deionized water, their surface properties remained almost unchanged, indicating that no soluble degradation products were generated on the surface of the fluorinated samples during the corona treatment process. The fluorinated layer has a high barrier to corona discharge. Fluorination improves the corona discharge resistance of epoxy insulation in carbon dioxide.
[0179] Embodiment 7:
[0180] The epoxy samples were corona treated using a multi-needle-plate electrode system in a plexiglass chamber filled with C4F7N / CO2 mixed gas.
[0181] After the fluorinated samples treated with corona were rinsed with deionized water, their surface properties remained almost unchanged, indicating that no soluble degradation products were generated on the surface of the fluorinated samples during the corona treatment process. The fluorinated layer has a high barrier to corona discharge. Fluorination improves the corona discharge resistance of epoxy insulation in C4F7N / CO2 mixed gas.
[0182] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.
Claims
1. A method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators, characterized in that The following steps are involved: Prepare epoxy insulation samples; Prepare a closed reactor; Configure fluorine-containing mixed gas; Fluoridation treatment; Take out the sample after cooling; Analyze the characteristics of the fluorinated layer; Evaluate charge accumulation and corona discharge performance; Perform a corona discharge test.
2. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The epoxy insulation sample comprises bisphenol A diglycidyl ether type epoxy resin solidified by methyltetrahydrophthalic anhydride filled with aluminum oxide particles; the epoxy insulation sample is a disc insulator.
3. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The production process of epoxy insulation samples is as follows: Bisphenol A diglycidyl ether and methyltetrahydrophthalic anhydride are uniformly mixed in a weight ratio of 1:1; during the mixing process, ensure that the two materials are fully mixed; the mixed material should be in a uniform liquid state without obvious stratification or precipitation; The mixed materials are subjected to vacuum degassing treatment; vacuum degassing removes bubbles and volatile impurities in the materials and improves the quality and performance of the samples; The degassed material is vacuum poured into a stainless steel mold; the pouring process should be done slowly to avoid bubbles and turbulence; The cast samples were cured at 140°C for 9 hours. During the curing process, the temperature was kept stable to avoid excessive temperature fluctuations. After curing, the sample should have a certain hardness and strength, and the surface should be smooth and flat; After curing, clean the sample to remove the release agent on its surface; The cleaned samples were dried in a vacuum oven at 50°C.
4. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The fluorine-containing mixed gas comprises fluorine gas and inert gas; the volume percentage of fluorine gas in the fluorine-containing mixed gas is 2% to 50%; Before using the reactor, replace the gas in the reactor with high-purity nitrogen at least 3 times to ensure that there is no other impurity gas in the reactor.
5. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The process of fluorination treatment is as follows: placing the epoxy insulation sample into a reactor; heating the reactor to a set temperature of 50°C; slowly introducing a fluorine-containing mixed gas to maintain a reaction pressure of 1 bar; and the reaction time is 30 minutes.
6. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 5, characterized in that: The reaction temperature of the fluorination treatment is from room temperature to 100°C.
7. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 5, characterized in that: The reaction pressure of the fluorination treatment is 0.1-2 bar.
8. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 5, characterized in that: The reaction time of the fluorination treatment is 10 min-24 h.
9. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The fluorination process is: Place the prepared epoxy insulation samples into the reactor; the samples should be evenly distributed in the reactor to avoid accumulation and overlap to ensure uniformity of fluorination treatment; Heat the reactor to the set temperature, the temperature range is: room temperature to 100 ° C; Slowly introduce the fluorine-containing mixed gas to maintain the reaction pressure at 0.1-2 bar. The pressure control should be adjusted according to the pressure resistance of the reactor and the requirements of fluorination treatment; The fluorine gas concentration is 12.5% of the fluorine-nitrogen mixed gas, and the reaction time is 10 minutes to 24 hours. The length of the reaction time should be adjusted according to the requirements of the fluorination treatment and the performance of the sample.
10. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 9, characterized in that: The process of taking out the sample after cooling is as follows: after the reaction is completed, turn off the heating source and cool naturally to room temperature; open the reactor and take out the epoxy insulation sample after fluorination treatment.
11. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 9, characterized in that: Analyzing the characteristics of the fluorinated layer means using a scanning electron microscope to observe the thickness of the fluorinated layer and its surface morphology. The process is as follows: The SEM cross-section samples were prepared by low-temperature brittle fracture in liquid nitrogen. Low-temperature brittle fracture prevented the samples from being affected by thermal and mechanical stresses during the preparation process, and maintained the original structure and performance of the samples. During the brittle fracture process, the samples were quickly immersed in liquid nitrogen, and then gently tapped with a hammer or other tool to break them. The broken samples should be immediately observed by SEM to avoid oxidation and contamination on the sample surface. The chemical composition and structure of the fluorinated layer were analyzed by attenuated total reflection infrared spectroscopy; attenuated total reflection infrared spectroscopy can provide chemical information on the surface of the sample and reveal the effect of fluorination treatment on the chemical structure of epoxy resin; Attenuated total reflection infrared spectroscopy uses germanium crystal as the reflective crystal for testing, and the spectrum is the average of 128 scans; multiple scans can improve the signal-to-noise ratio and accuracy of the spectrum and reduce the impact of noise and errors; Ensure that the thickness of the fluoride layer is between 0.2-2 μm.
12. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The procedure for evaluating charge accumulation and corona discharge performance is: The sample is charged by gate control. Gate control charging can provide a uniform electric field to avoid local discharge and charge accumulation on the surface of the sample. Inside the material, the charge transport process to the ground electrode is described by the current conduction equation, Poisson's equation and charge continuity equation: j e (x,t)=γE(x,t) (1); in, Where x is the medium depth in m; t is the time in s; γ is the Poole-Frenkel conductivity of the medium material in S·m -1 ; When there is no external electric field, the bulk conductivity of the medium at temperature T is γ0(T), the unit is S·m -1 ; e is the electron charge, the unit is C; j e (x, t) is the current density, in A·m -2 ; q(x,t) is the charge density, the unit is C·m -3 ; E(x,t) is the electric field strength, the unit is V·m -1 ; Before charging, the sample should be placed in a suitable electrode system to ensure good contact between the sample and the electrode; The experimental conditions were set as follows: needle voltage: 10 kV, grid voltage: 2 kV, charging time: 5 minutes; Quickly transfer the sample to the bottom of the potential detector to measure the surface potential; the potential detector should have the characteristics of high sensitivity and fast response, and be able to accurately measure the potential change on the surface of the sample; during the measurement process, the distance between the sample and the potential detector should be kept stable to avoid the influence of distance changes on the measurement results; Use a multi-function meter to transfer the measured data to a computer to record the charge dissipation rate; the multi-function meter should have the characteristics of high precision and high stability, and be able to accurately record the potential change and charge dissipation rate on the surface of the sample; when recording data, pay attention to the accuracy and reliability of the data to avoid data errors and losses; The charge accumulation and corona discharge performance were evaluated in a plexiglass chamber filled with air, carbon dioxide or C4F7N / CO2 mixed gas; the samples were corona treated using a multi-needle-plate electrode system; the surface changes of the samples during the corona discharge process were recorded and the corona erosion was evaluated; The evaluation was performed in a plexiglass chamber filled with air, carbon dioxide, or a C4F7N / CO2 mixture; The sample is corona treated using a multi-needle-plate electrode system; the multi-needle-plate electrode system is used to provide a uniform electric field to avoid partial discharge and corona discharge on the surface of the sample; before corona treatment, the sample is placed in a suitable electrode system to ensure that the distance and angle between the sample and the electrode meet the requirements; The size of the upper electrode plate is 380×320mm, with a total of 280 tungsten needles evenly distributed on the upper electrode plate. The grounded stainless steel electrode consists of a fixed frame plate and a rotatable disc. The sample is placed on the disc and rotates at a speed of 1 circle per minute. The electrode system was placed in a sealed plexiglass chamber. The original epoxy resin sample and the surface fluorinated sample were corona treated at room temperature. The gas in the chamber was evacuated and filled with 0.1MPa high-purity nitrogen. An AC voltage of 50Hz and 14kV was applied to the high-voltage electrode. The gas in the chamber was replaced every 12 hours, and the total treatment time was 120h.
13. The method for optimizing the corona discharge resistance and charge accumulation of epoxy insulators according to claim 1, characterized in that: The corona discharge tests are: Ultrasonic cleaning: ultrasonic cleaning is performed on the original samples and fluorinated samples after corona treatment; ultrasonic cleaning can remove pollutants and degradation products on the surface of the samples, and improve the surface cleanliness and performance of the samples; during the cleaning process, appropriate cleaning agents and cleaning time should be selected to avoid the cleaning agent affecting the performance of the samples; Water contact angle measurement: measure the water contact angle of the original sample; the water contact angle is an important indicator to measure the wettability of the sample surface. The smaller the water contact angle, the better the wettability of the sample surface; when measuring the water contact angle, deionized water should be used as the test liquid, drop water on the sample surface, and then use a contact angle meter to measure the contact angle between the water drop and the sample surface; measure the water contact angle of the sample after ultrasonic cleaning; the surface of the sample after ultrasonic cleaning may change, so the water contact angle needs to be measured again to evaluate the cleaning effect and the surface performance of the sample; Corona resistance evaluation: Compare the contact angles of samples under different treatment conditions to evaluate the corona resistance of the fluorinated layer; By comparing the water contact angles of the original sample, the fluorinated sample and the sample after ultrasonic cleaning, the effect of the fluorinated layer on the wettability of the sample surface and the corona resistance of the fluorinated layer can be evaluated; generally speaking, the fluorinated layer can reduce the water contact angle on the sample surface, improve the surface wettability of the sample, and also improve the corona resistance of the sample.